ЎАҚЫТЛЫ БАСПАСӨЗДЕ ҚАРАҚАЛПАҚ ПОЭЗИЯСЫ МӘСЕЛЕЛЕРИ(1990-2000 жж) - Алланазарова, З. (ILIM hám JÁMIYET, 2025)
In Karakalpak literary criticism, the genre of review mainly studies poetry issues in detail. The article analyzes literary critical materials published in the 1990-2000s in the journal "Amiudarya" and the newspapers "Erkin Karakalpakstan", "Karakalpakstan Jaslari", "Ustaz" ("The Way of the Teacher").